Horizontal acquisition of hydrogen conversion ability and other habitat adaptations in the Hydrogenovibrio strains SP-41 and XCL-2 - Giorgio Gonnella; Nicole Adam; Mirjam Perner (BMC Genomics, 2019)
Abstract Background Obligate sulfur oxidizing chemolithoauthotrophic strains of Hydrogenovibrio crunogenus have been isolated from multiple hydrothermal vent associated habitats. However, a hydrogenase gene cluster (encoding the hydrogen converting enzyme and its maturation/assembly machinery) detected on the first sequenced H. crunogenus strain (XCL-2) suggested that hydrogen conversion may also play a role in this organism. Yet, numerous experiments have underlined XCL-2’s inability to consume hydrogen under the tested conditions. A recent study showed that the closely related strain SP-41 contains a homolog of the XCL-2 hydrogenase (a group 1b [NiFe]-hydrogenase), but that it can indeed use hydrogen. Hence, the question remained unresolved, why SP-41 is capable of using hydrogen, while XCL-2 is not. Results Here, we present the genome sequence of the SP-41 strain and compare it to that of the XCL-2 strain. We show that the chromosome of SP-41 codes for a further hydrogenase gene cluster, including two additional hydrogenases: the first appears to be a group 1d periplasmic membrane-anchored hydrogenase, and the second a group 2b sensory hydrogenase. The region where these genes are located was likely acquired horizontally and exhibits similarity to other Hydrogenovibrio species (H. thermophilus MA2-6 and H. marinus MH-110 T ) and other hydrogen oxidizing Proteobacteria (Cupriavidus necator H16 and Ghiorsea bivora TAG-1 T ). The genomes of XCL-2 and SP-41 show a strong conservation in gene order. However, several short genomic regions are not contained in the genome of the other strain. These exclusive regions are often associated with signs of DNA mobility, such as genes coding for transposases. They code for transport systems and/or extend the metabolic potential of the strains. Conclusions Our results suggest that horizontal gene transfer plays an important role in shaping the genomes of these strains, as a likely mechanism for habitat adaptation, including, but not limited to the transfer of the hydrogen conversion ability.